Cardiologic scoring system as predictors of mortality in geriatric COVID-19 patients - Yudi Her Oktaviono; Makhyan Jibril Al Farabi; Aurelia Regina; Audrey Florencia Theno; Ariikah Dyah Lamara (Journal of the Pakistan Medical Association, 2024)
Objective: To develop a cardiologic scoring system to predict mortality among geriatric coronavirus disease-2019 patients. Method: The retrospective cohort study was conducted after approval from the ethics review committee of the Dr Soetomo General Academic Hospital, Surabaya, Indonesia, and comprised data from March 1, 2020, to April 30, 2021, of geriatric patients of either gender confirmed for coronavirus disease-2019 from several referral hospitals in East Java, Indonesia. Data on comorbidities, electrocardiograph, and chest X-ray findings was examined to develop a comprehensive scoring system. Data was analysed using SPSS 26. Results: Of the 3,893 cases reviewed, data of 322(8.27%) patients was analysed; 191(59.3%) males and 131(40.7%) females. The overall mean age was 66±4.1 years (range: 60-75 years). Of them, 267(82.9%) subjects were alive upon hospital discharge, while 55(17.1%) died during hospitalisation. Of the 24 variables analysed, 5(21%) were found to be significant: cardiomegaly, sinus tachycardia, ST-segment abnormalities, pathological T-wave inversions, and axis deviation (p<0.05). Receiver operating characteristic curve analysis showed an area under the curve 0.86, cut-off point Less Than or Equal 4 with sensitivity 89% and specificity 69%. Conclusion: The scoring system was found to have the potential to predict mortality in geriatric coronavirus disease-2019 patients based on cardiac findings during hospital admission. Key Words: Cardiovascular, COVID-19, Electrocardiography, Arrhythmia, Cardiomegaly, Tachycardia.